An eBook is not a book is not a book - Theodorou, Roxana (Qualitative and Quantitative Methods in Libraries; Vol 4 No 1 (2015): March 2015 Issue, 2017)
A while back I started reading Gertrud Stein. Maybe I tried to embrace poetry a little late in life, however better late than never. The truth is that poetry is not an “obvious” thing, not always, so I tried to accompany my poetry books with several studies about them. And just like that, I stumbled upon Sacred Emily and the sentence “Rose is a rose is a rose is a rose”. That didn’t need any explaining. It was pretty obvious: things are what they are. But, it goes a little deeper than that. In Stein’s view, the sentence expresses the fact that simply using the name of a thing already invokes the imagery and emotions associated with it, an idea also intensively discussed in the problems of universal debate where Peter Abelard and others used the rose as an example concept. (Wikipedia, 2013)